Development Strategy of Village-Owned Enterprises (BUMDes) Bumi Sari in Natar District, South Lampung - Hamid, Achmad Zuhri; Devia, Astri; Novalia (Universitas Muhammadiyah Pontianak, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in strengthening rural economies; however, many face managerial and strategic limitations. This study aims to formulate a development strategy for BUMDes Bumi Sari in Natar District, South Lampung. A descriptive qualitative approach was employed, with data collected through interviews, observation, and documentation, analyzed using SWOT analysis. The findings indicate strong government support and local resource potential, but weaknesses in human resource capacity and governance. The recommended WO strategy emphasizes managerial improvement, digitalization, and business diversification. These strategies are expected to enhance sustainability and strengthen rural economic empowerment.